Retinal status in moderate myopia and age-related macular degeneration. Management strategies - L.K. Moshetova; I.B. Alekseev; I.V. Vorobyeva; Yu.A. Nam (РМЖ "Клиническая офтальмология")
L.K. Moshetova1, I.B. Alekseev1–3, I.V. Vorob’eva1,2, Yu.A. Nam3 1Russian Medical Academy of Continuous Professional Education, Moscow,  Russian Federation 2S.P. Botkin City Clinical Hospital, Moscow, Russian Federation 3Treatment Rehabilitation Center of the Ministry of Economic Development, Moscow,  Russian Federation Aim: to assess retinal status in comorbid ocular disorders (moderate myopia and age-related macular degeneration/AMD of various stages) using modern diagnostic tools. Patients and Methods: 48 patients (96 eyes) with moderate myopia and dry AMD were enrolled. Best-corrected visual acuity (BCVA), mean deviation/MD (characterizes mean reduction of sensitivity), pattern standard deviation/PSD (characterizes the severity of local visual field defects), central macular thickness (CMT), and axial length (AL) were measured. The macular zone was investigated by optical coherence tomography (OCT) using B scan and fundus autofluorescence (FAF) regimens. Results: in moderate myopia associated with dry AMD (AREDS categories 1,2,3), a significant reduction in the mean BCVA (20/25) was detected in 54.2% (26 patients, 52 eyes). Retinal photosensitivity indices (MD and PSD) were also significantly reduced to 2.19 dB (р<0.001) and 2.14 dB (р<0.001), respectively. AL was significantly increased (25.11 mm, р<0.001). No significant differences in CMT values were revealed (233 mcm, p=0.123). In comorbid ocular disorders, severe defects and focuses of RPE atrophy, extensive areas of the IS/OS junction line damage, and drusen are seen among morphological abnormalities of the eye fundus. FAF identified certain pathological patterns, e.g., focal hypo- and hyperautofluorescence, hyperautofluorescent halo at the border of staphyloma, linear hypoautofluorescent bands surrounded with hyperautofluorescence, reticular pattern, patches, focal and multifocal areas of geographic atrophy. Conclusion: our findings on visual field loss (MD, PSD) in AMD depending on stage and OCT findings in AMD are in line with the results of other authors. Meanwhile, we investigated a comorbid variant (AMD in association with moderate myopia), compared morphological and functional parameters, and addressed the relevance of FAF. Keywords: myopia, age-related macular degeneration, optical coherence tomography, autofluorescence. For citation: Moshetova L.K., Alekseev I.B., Vorob’eva I.V., Nam Yu.A. Retinal status in moderate myopia and age-related macular degeneration. Management strategies. Russian Journal of Clinical Ophthalmology. 2022;22(2):91–98 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-91-98.